تقويم كفاءة إدارة الموانئ دراسة ميدانية لمرفأي اللاذقية وطرطوس - ديوب, محمد عباس (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث تقويم أداء إدارة الموانئ, وذلك من خلال دراسة مجموعة من المؤشرات الأساسية التي تحدد كفاءة إدارة الموانئ ودراسة تحليلية واقعية لمرفأي اللاذقية وطرطوس من أجل تحديد مستوى كفاءة أداء هذين المرفأين وإيجاد العلاقات بين مجموعة من المتغيرات التي تساعد في تحديد مستوى الكفاءة. تم التعرض في البحث إلى مجموعة من الجوانب التي تسهم في إغناء البحث, ومن أهمها تصنيف الموانئ وتكاليف النقل البحري وتكاليف السفينة ومعايير قياس أداء الانجاز في الموانئ, بالإضافة إلى مجموعة مؤشرات كفاءة إدارة الموانئ, مثل عدد الركاب والإيرادات وحركة البواخر والبضائع وإنتاجية اليد العاملة وقد توصل الباحث إلى مجموعة من النتائج وأهمها: - زيادة كبيرة في حركة البواخر وحركة البضائع والترانزيت. - زيادة كبيرة في إيرادات المرفأين. - زيادة كبيرة في إنتاجية اليد العاملة. - وجود علاقة قوية بين حركة البواخر والإيرادات وبين الإيرادات وحركة البضائع. The research deals with the performance evaluation of port management. This is done studying some fundamental indictors which identify the effectiveness of port management. It also analyzes the status of Lattakia and Tartous ports in order to identify their level of performance effectiveness and explore the relations found among some variables needed to measure the level of effectiveness. The study also presents some aspects which contribute to enriching this investigation. Most important, the classification of ports, marine transport costs, ship costs, and the measurement standards of ports performance. Additionally, there have been some other effectiveness indicators such as number of passengers, revenues, the number of ships sailings and quantities of commodities, as well as the manpower productivity. As a result, few important conclusions have been reached: • a noticeable increase in the number of ships sailings and quantities of commodities; • a noticeable increase in the revenues ports; • a noticeable increase in the manpower productivity; • a strong association between the number of ships sailings and the revenues on one side, and between the revenue and quantities of commodities;